Massive Open Online Courses (MOOCs) and their effect on learners motivation - Elsayed Mohamed, Umniya Usama; Md Ali, Asma (Institute of Electrical and Electronics Engineers Inc., 2018)
Massive Open Online Course (MOOC) have become a new form innovation whose development has shown great challenges to the traditional classroom mode of teaching, they have also proven to be an alternative way of delivering interactive teaching as well as learning. The aim of this paper is to determine the key factors affecting student motivation in course completion as well as the approaches used by teachers to ensure that the students complete the course. To help in building a better understanding, an in-depth interview was conducted with a course facilitator at the International Islamic University. To get the students perspective on learning through MOOCS, a survey was distributed among students from several universities across Malaysia. The purpose of this survey was to probe students motivation, learning perceptions, and experiences towards MOOCS, focusing on MOOCS affordances and challenges that may lead to high dropout rates. This research paper has helped identify the learning motivations, learning styles, and a number of factors that appear to influence student motivation. © 2018 IEEE.